A Systematic Review of the Trends Thin Film Characteristics Research as Electronic Device (2015-2024) - Susilawati Susilawati; Aris Doyan; Agus Abi Purwoko; Ibrahim Ibrahim; Sukainil Ahzan; Sifaul Gummah; Bahtiar Bahtiar; Muhammad Ikhsan; Syamsul Hakim; Lalu Muliyadi; Haris Munandar (Jurnal Penelitian Pendidikan IPA, 2024)
Thin film characteristics are the properties possessed by the thin film, both physical and chemical properties. The characteristics of this thin film are influenced by several factors, namely the material that makes up the thin film, the thin film deposition method, and the conditions of the thin film deposition process. This research aims to identify and analyze research trends in the characteristics of thin films as electronic devices. This research method is descriptive and analytical. The data used in this research was obtained from documents indexed by Google Scholar from 2015-2024 using Publish or Perish and Dimension.ai. Research procedures use PRISMA guidelines. The data identified and analyzed are the type of publication, publication source, and the title of research on thin film synthesis that is widely cited. The data analysis method uses bibliometric analysis assisted by VOSviewer software. The results of the analysis show that the trend of research on the characteristics of thin films as electronic devices indexed by Google Scholar from 2015 to 2024 experienced a fluctuating increase, however, in 2023 there was a decline in the trend of research on the characteristics of thin films as electronic devices. There are many documents in the form of articles, proceedings, book chapters, preprints, and edited books that discuss research into the characteristics of thin films as electronic devices. Key words that are often used in research on the characteristics of thin films as electronic devices are thin film coating, heat transfer characteristic, film characteristic, and photovoltaic characteristic.